M/BiOCl‐(M = Pt, Pd, and Au) Boosted Selective Photocatalytic CO2 Reduction to C2 Hydrocarbons via *CHO Intermediate Manipulation - Qiong Liu; Chengbo Bai; Chengxin Zhu; Wenjin Guo; Guangfang Li; Sheng Guo; Devesh Kripalani; Kun Zhou; Rong Chen (Advanced Science)
Abstract Selective CO2 photoreduction to C2 hydrocarbons is significant but limited by the inadequate adsorption strength of the reaction intermediates and low efficiency of proton transfer. Herein, an ameliorative *CO adsorption and H2O activation strategy is realized via decorating bismuth oxychloride (BiOCl) nanostructures with different metal (Pt, Pd, and Au) species. Experimental and theoretical calculation results reveal that distinct *CO binding energies and *H acquisition abilities of the metal cocatalysts mediate the CO2 reduction activity and hydrocarbon selectivity. The relatively moderate *CO adsorption and *H supply over Pd/BiOCl endows it with the lowest free energy to generate *CHO, leading to its highest activity of hydrocarbon production. Specifically, the Pt cocatalyst can efficiently participate in H2O dissociation to deliver more *H for facilitating the protonation of the *CHO and *CHOH, thereby favoring CH4 production with 76.51% selectivity. A lower *H supply over Pd/BiOCl and Au/BiOCl results in a large energy barrier for *CHO or *CHOH protonation and thus a more thermodynamically favored OC─CHO coupling pathway, which endows them with vastly increased C2 hydrocarbon selectivity of 81.21% and 92.81%, respectively. The understanding of efficient C2 hydrocarbon production in this study sheds light on how materials can be engineered for photocatalytic CO2 reduction.